2017
DOI: 10.1016/j.abb.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The cardiomyopathy-associated K15N mutation in tropomyosin alters actin filament pointed end dynamics

Abstract: Correct assembly of thin filaments composed of actin and actin-binding proteins is of crucial importance for properly functioning muscle cells. Tropomyosin (Tpm) mediates the binding of tropomodulin (Tmod) and leiomodin (Lmod) at the slow-growing, or pointed, ends of the thin filaments. Together these proteins regulate thin filament lengths and actin dynamics in cardiac muscle. The K15N mutation in the TPM1 gene is associated with familial dilated cardiomyopathy (DCM) but the effect of this mutation on Tpm's f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…However, the physiologic manifestations of various myopathic mutations of Tpm are multifaceted, so we cannot exclude the notion that they may affect its other properties. In recent studies, it has been found that mutations in Tpm genes can lead to changes in its interaction not only with the main proteins of thin and thick filaments, i.e., with actin and myosin, but also with tropomodulin and nebulin, which can affect sarcomere structure (48,49). The investigation of the mechanisms of interaction of the ab-heterodimer bearing various myopathic mutations with different partner proteins of actin filament in muscle cells is of great importance for a more detailed understanding of the development of myopathy and muscle functioning in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiologic manifestations of various myopathic mutations of Tpm are multifaceted, so we cannot exclude the notion that they may affect its other properties. In recent studies, it has been found that mutations in Tpm genes can lead to changes in its interaction not only with the main proteins of thin and thick filaments, i.e., with actin and myosin, but also with tropomodulin and nebulin, which can affect sarcomere structure (48,49). The investigation of the mechanisms of interaction of the ab-heterodimer bearing various myopathic mutations with different partner proteins of actin filament in muscle cells is of great importance for a more detailed understanding of the development of myopathy and muscle functioning in general.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of G‐actin polymerization rates by Tmod1, in the presence of wild‐type and mutant Tpm3.12, was analyzed by following fluorescence increase of pyrene‐G‐actin as described in . F‐actin seeds were prepared by incubation of 3 μ m unlabeled G‐actin with 30 n m gelsolin in: 25 m m imidazole, pH 7.0, 0.1 m KCl, 2 m m MgCl 2 , 0.2 m m ATP, 1 m m DTT, 1 m m EGTA, for 1 h. Seeds were diluted five‐fold with a solution of 1.0 μ m Pyrene‐labeled (5%) G‐actin in the presence or absence of 2.5 μ m Tpm3.12, 2.5 μ m Tpm3.12‐A4V, or 3.0 μ m Tpm3.12‐R91C.…”
Section: Methodsmentioning
confidence: 99%
“…The DCM-causing Lys15Asn decreases the affinity of Tpm1.1 to the tropomyosin-binding site of Lmod2 and both tropomyosin-binding sites of Tmod1. Defects in the interactions between the N-terminal segment of the mutant tropomyosin and the isolated tropomyosin-binding sites of Lmod2 and Tmod1 result in significantly reduced binding of full length proteins and impaired abilities to inhibit elongation of the pointed end (Colpan et al 2017). The HCMlinked mutation Arg21His causes a severe decrease in the affinity for the isolated tropomyosin binding site of Lmod2 and diminishes the ability of Lmod2 to inhibit elongation of the pointed end (Ly et al 2019).…”
Section: Mutations In Tpm11 and Tpm312 As Tools In The Studies On Tmentioning
confidence: 99%